(untitled) (Texas Journal of Medical Science, 2023)
The prevalence of cancer is steadily increasing every year and, most likely, will continue to grow in the future, which means that malignant neoplasms need to be detected as early as possible and treated as accurately as possible. Despite certain advances in diagnostics and treatment methods, the rate of increase in cancer incidence is steadily increasing. Treating patients with cancer is challenging. That is why the problem of choosing adequate treatment regimens and choosing innovative drugs in the field of oncology is relevant today. At the moment, modern oncology of anticancer drugs has changed traditional methods for testing new anticancer drugs and assessing their effectiveness through the introduction of large multicenter randomized studies, the indications for the use of existing drugs are being expanded and new ones are being introduced.